Understory Vegetation in Oil Palm Plantations Benefits Soil Biodiversity and Decomposition Rates - Ashton-Butt, Adham; Aryawan, Anak A. K.; Hood, Amelia S. C.; Naim, Mohammad; Purnomo, Dedi; Suhardi,; Wahyuningsih, Resti; Willcock, Simon; Poppy, Guy M.; Caliman, Jean-Pierre; Turner, Edgar C.; Foster, William A.; et al. (Frontiers in Forests and Global Change, 2018)
Oil palm is the most productive oil crop per unit area and is crucial to the economy of developing countries such as Malaysia and Indonesia. However, it is also highly controversial due to the impact it has on biodiversity. Inputs of herbicides to control understory vegetation in plantations are high, which is likely to harm native biodiversity, but may be unnecessary in protecting oil palm yield. In this study we investigate the effects of understory manipulation using herbicides on soil fauna, litter decomposition rates and soil abiotic variables: pH, soil organic carbon, soil water content, nitrogen, carbon/nitrogen ratio, potassium and phosphorous. Understory vegetation was manipulated in three treatments: enhanced (no herbicides), normal (intermediate herbicide use) and reduced treatments (heavy herbicide use). Two years after treatment, soil macrofauna diversity was higher in the enhanced than the normal and reduced understory treatment. Furthermore, both macrofauna abundance and litter decomposition was higher in the enhanced than the reduced understory treatment. By contrast, soil fertility did not change between treatments, perhaps indicating there is little competition between oil palms and understory vegetation. The reduction of herbicide use should be encouraged in oil palm plantations, this will not only reduce plantation costs, but improve soil biodiversity and ecosystem functioning.